Stratigraphic distribution, taphonomy and paleoenvironments of Spinicaudata in the Triassic and Jurassic of the Paraná Basin. (December 2017) - Jenisch, Alan Gregory; Lehn, Ilana; Gallego, Oscar Florencio; Monferran, Mateo Daniel; Horodyski, Rodrigo Scalise; Faccini, Ubiratan Ferrucio
Abstract: Due to the chitino-phosphatic nature of Spinicaudata conchostracan exoskeletons, their carapaces exhibit a low preservational potential compared to other bivalve groups. However, the recent studies point towards the increased tolerance of the carapace against the physical processes. Due to this peculiar characteristic, conchostracan carapace have been utilized as precise temporal markers in estimating stratigraphic and taphonomic parameters. The same characteristic also makes the spinicaudatans useful in evaluating the depositional processes and environments. The present work aims at providing a paleoenvironmental and stratigraphic analysis of conchostracans (Spinicaudata) from the Triassic-Jurassic of the Paraná Basin (Santa Maria and Caturrita formations) in terms of the sedimentary facies analysis, depositional system characterization, and analysis of the taphonomic signatures of the fossiliferous horizons within these formations. The results from the taphonomic study delineates the presence of 4 distinct fossil assemblages based on the causative mechanism and fundamental characteristics of the fossil concentrations: two taphonomic assemblages in the laminated mudstone beds deposited from the decanting fine-grained sediments in floodplains; the sandstone beds with plane parallel laminations and dune- and ripple-cross-stratifications deposited from the flooding-related overflow in the floodplains; and the association of laminated mudstone and massive sandstone beds deposited as the river mouth bars. The results show that the taphonomic signatures, e.g., closed valves, may indicate the various patterns of autochthony and allochthony. In the fine-grained floodplain assemblages, the high degree of preservation can be attributed to autochthony in the conchostracans, whereas the preservational condition of floodplain sandstone sheet and mouth bar assemblages point toward parautochthony and even allochthony. Therefore, the preservational quality of conchostracan exoskeletons is likely a function of parameters, e.g., the transport duration, the distance from life position, and the magnitude of events causing their final burial. Within the observed species, the recognition of Eustheria minuta in the stratigraphic level of the Passo das Tropas creek corroborates an age for these deposits between the late Middle Triassic and early Upper Triassic. The presence of a new form, likely related to the family Fushunograptidae in sediments from the Caturrita Formation, suggests a Jurassic age for these deposits. Highlights: It is integrated between taphonomy and sedimentary geology for continental underwater macroinvertebrates of the Paraná Basin. The data presented here show that taphonomic signatures may indicate different patterns of autochthony/allochthony. The conchostráceos presented a distribution of the Middle Triassic until possibly Lower.